Development of tools for studying Olea europaea: Pseudomonas savastanoi interaction - Cruz, A. Braga da (2002)
Poster apresentado no 13th Congress of the Federation of European Societies of Plant Physiology, em 2002, Hersonissos, Creta, Grécia